Changing of the guards: private influences, privatization, and criminal justice in Canada - Luscombe, Alex; Walby, Kevin; Silva, Derek M. D. (UBC Press, 2022)
"Although service outsourcing has spread throughout Canada's prisons and jails, into its police, courts, and national security institutions, and along the border in recent decades, the expanding scope and pace of corporate involvement in criminal justice functions has not yet been closely investigated. Changing of the Guards provides a detailed assessment of privatization and private influence across the twenty-first-century Canadian criminal justice system. It illuminates the many consequences of public-private arrangements for law and policy, transparency, accountability, the administration of justice, equity, and the public. This trenchant analysis raises issues that are relevant in Canada and abroad."--